2005
DOI: 10.1002/fam.893
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen chloride evolution from the heating of poly(vinyl chloride) compounds

Abstract: SUMMARYThe dehydrochlorination and the thermal decomposition of five PVC materials was studied using two techniques: a batch analytical method, combining ion chromatography and atomic absorption and continuous thermogravimetry. The temperatures studied ranged from 608C to 1208C, over a period of almost one year (50 weeks). It was found that a very large proportion of the soluble chloride emitted early on by the PVC materials into the liquid phase is not hydrogen chloride. None of the five materials tested emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…As far as the temperature effect is concerned, the decrease of the calcium/zinc carboxylates bands on the inner surface of the tube, both for sterilized and nonsterilized samples, as a function of temperature ( Figure 2), could be ascribed to a migration phenomena of the heat stabilizers in the plastic polymer material from the surface to the bulk of the tubes or, otherwise, to reaction mechanisms of the additives themselves as a consequence of the heat treatments. Nevertheless, the latter explanation does not completely justify the experimental evidences obtained for nonsterilized samples at temperatures up to 70 • C, where the HCl formation should be negligible [34].…”
Section: Resultsmentioning
confidence: 80%
“…As far as the temperature effect is concerned, the decrease of the calcium/zinc carboxylates bands on the inner surface of the tube, both for sterilized and nonsterilized samples, as a function of temperature ( Figure 2), could be ascribed to a migration phenomena of the heat stabilizers in the plastic polymer material from the surface to the bulk of the tubes or, otherwise, to reaction mechanisms of the additives themselves as a consequence of the heat treatments. Nevertheless, the latter explanation does not completely justify the experimental evidences obtained for nonsterilized samples at temperatures up to 70 • C, where the HCl formation should be negligible [34].…”
Section: Resultsmentioning
confidence: 80%
“…The Brebu's work [9], who studied waste medium voltage cables (6 -10 kV) after 18 years of operation, concludes that the PVC's deshycloration is very low under service conditions. Indeed, according Hishler [8], it would take at least 2 billion years to have a release of 1% by mass of HCl at 40˚C. clearly, this estimate has no physical significance since the material itself will not survive that many years, but it does confirm that deshychloration of PVC is a negligible phenomenon at low, near ambient temperatures.…”
Section: Results Presentation On the Total Resistance Of The Cablementioning
confidence: 97%
“…A good insulation essentially means a relatively high resistance to current. In order to describe an insulating material, a good insulation also means "the ability to maintain a high resistance" [8].…”
Section: Results Presentation On the Total Resistance Of The Cablementioning
confidence: 99%
See 1 more Smart Citation
“…Van Luik [8] studied the production of sub-micron particles and found that PVC wire insulation produced 'large numbers' of these by the time that 1438C was attained. Hirschler [9] tested in air a flexible-PVC compound used for wire/cable making and found essentially no HCl emission at 908C, with measurable emissions occurring at 1058C, which is broadly similar to the temperature range found for pure PVC. Other investigators examining similar PVC wire/cable materials reported higher degradation temperatures, presumably due to use of experimental techniques not well suited to lower temperature regimes.…”
Section: Introductionmentioning
confidence: 99%